Declaring the Value of Truth: Progressive-era lessons for combatting fake news. (16th March 2019) - Creech, Brian; Roessner, Amber
Abstract : As fake news has become a growing concern since the 2016 U.S. presidential election, attention to journalism history offers a useful means for rediscovering strategies for both fighting fake news and shoring up journalism's commitment to the truth. This article argues that truth's value emerges from the conditions under which journalism is produced, both commercial and cultural. Looking at arguments about fake news published in news reports, columns, letters to editors, and advertisements in major metropolitan papers between 1891 and 1919, we recover the particular ways journalists came to define the problem of fake news, arguing that its emergence as a discursive object offered opportunities for conceiving of and articulating practicable responses across the industry. For contemporary practitioners, scholars, and commentators alike, this means that clearly defining and responding to the problem of fake news in ways that are both critical and contextual offer a means for recovering agency in the face of this crisis.